Daily field checking list by Walter Rosene, April 2, 1939 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed in Boone County by Walter Rosene and Bob Walker, April 2, 1939. Also notes the Great Horned Owl nest contained food consisting of animal remains. Plustek--flatbed